MODEL-MODEL LEMBAGA PENDIDIKAN ISLAM - Dede Rubai Misbahul Alam; Urmila Pandra Kartika; Ummu Athiyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic educational institutions are entities or bodies that regulate and implement Islamic education, having an organized structure and responsibility for the implementation of Islamic education. Therefore, these Islamic educational institutions must be able to create an environment that supports the effective implementation of education in accordance with their roles and duties, such as schools (madrasahs) that are responsible for the Islamic education process. The purpose of this study is to find and analyze the Models of Islamic Educational Institutions. This research uses a library research approach, which involves describing phenomena or concepts based on existing literature sources and theories, concepts, or results from previous research. The results of this study indicate that through comprehensive religious teaching, pesantrens help build a strong understanding of Islamic values, ethics, and morality. Thus, pesantrens play an important role in shaping an individual's character and spirituality, which in turn will have a positive impact on the social life of the community.